2006
DOI: 10.1038/sj.ijo.0803210
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal obesity, systolic blood pressure, and microalbuminuria in normotensive and euglycemic Korean men

Abstract: Objectives: To evaluate the relationship between abdominal obesity and microalbuminuria (MA) in normotensive, euglycemic Korean men. Design: A cross-sectional study at a health screening center. Subjects: A total of 1321 healthy, normotensive Korean men, aged 20-78 years, with a fasting plasma glucose level o100 mg/dl. Measurements: Height, weight, and waist; systolic blood pressure (SBP); diastolic blood pressures (DBP); urinary albumin to creatinine ratio (ACR); fasting glucose, insulin, lipids, C-reactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…This theory is based on previous studies which have been conducted among populations with different proportions of hypertension, diabetes, and renal dysfunction, which are linked with a risk of CVD. Cross-sectional studies for individuals with neither hypertension nor diabetes have demonstrated that microalbuminuria was associated with waist circumference [31], SBP [31], serum CRP levels [32]. Our findings suggest that, in normotensive individuals with no diabetes, the association between albuminuria and a risk of CVD was unlikely to be through blood pressure and inflammation, as this association remained significant after adjustment for SBP and hsCRP levels.…”
Section: Discussionmentioning
confidence: 57%
“…This theory is based on previous studies which have been conducted among populations with different proportions of hypertension, diabetes, and renal dysfunction, which are linked with a risk of CVD. Cross-sectional studies for individuals with neither hypertension nor diabetes have demonstrated that microalbuminuria was associated with waist circumference [31], SBP [31], serum CRP levels [32]. Our findings suggest that, in normotensive individuals with no diabetes, the association between albuminuria and a risk of CVD was unlikely to be through blood pressure and inflammation, as this association remained significant after adjustment for SBP and hsCRP levels.…”
Section: Discussionmentioning
confidence: 57%
“…However, there might be several explanations underlying the effects of NAFLD on CKD. There is increasing evidence that obesity (visceral adiposity) may damage the kidney in otherwise healthy subjects [21][22][23]. Nonalcoholic fatty liver disease as a phenotype of excessive adiposity beyond normal liporegulation might be associated with CKD.…”
Section: Discussionmentioning
confidence: 97%
“…Ferris et al also found an association between MA and BMI, but only in patients with BMI ≥35 kg/m 2 [29]. In contrast, Chang et al did not find any significant relationship between BMI and MA in healthy, normotensive, euglycemic Korean men and suggested that only WC and systolic blood pressure (SBP) were independent predictors of MA [30]. These observations were supported by results from the multinational, multicenter large population study conducted by Thoenes et al on over 20 000 hypertensive out-patients from 26 countries [31].…”
Section: Discussionmentioning
confidence: 99%